Endovascular Treatment of Aneurysms of the Popliteal Artery by a Covered Endoprosthesis. Issue 8 (January 2014) - Wissgott, Christian; Lüdtke, Christopher W.; Vieweg, Hendryk; Scheer, Fabian; Lichtenberg, Michael; Schlöricke, Erik; Andresen, Reimer
Purpose: The current gold standard of popliteal artery aneurysm (PAA) treatment is saphenous vein bypass grafting. The aim of this retrospective single-center study is to investigate the safety and efficacy in the treatment of PAA by an endovascular implanted covered endoprosthesis. Materials and Methods: Ten patients, mean age 64.6 (range, 52-78) years, with PAA were treated with an expanded Polytetrafluoroethylen (ePTFE)-covered stent graft (Viabahn®, W.L. Gore and Associates Inc, Flagstaff, AZ, USA). In median, 1.4 prostheses were implanted with a median length of 180 mm. Follow-up visits included determination of ankle-brachial index (ABI) and color-coded duplex sonography. Results: The technical success rate was 100% (10/10). Clinically, there was an increase in ABI from 0.62 ± 0.17 to 0.91 ± 0.15 postinterventionally and to 0.89 ± 0.16 after an average follow-up of 24.7 months. During the follow-up period, 2 (20%) stent occlusions occurred; both of them were treated with a bypass graft. Conclusion: The treatment of PAA with covered endoprosthesis is a safe and effective alternative to open surgical therapy, where open surgical therapy is contraindicated or patient refused open surgery.